The ACTN3 R577Xgth in Korea national combat athletes - Min, S.-K.; Jee, E.; Lee, K.; Kim, J.; Lim, S.-T. (Science & Sports, 2021)
The aim of the present study is the investigation of the association between the ACTN3 genotype and the grip strength according to measurements in Korea National combats athletes. Fifty-six Korea National combats athletes (Judo and wrestling, male = 38, female = 18) and two hundred and twenty-one control group of normal populations (male = 135, female = 86) were recruited for the present study. The variables under examination were body composition, Wingate anaerobic test, and handgrip strength. Genotyping for the ACTN3 (rs 1815739) polymorphism was performed using the TaqMan approach. ACTN3 gene distribution of subjects was in the Hardy-Weinberg equilibrium (athletes: P = 0.175; control: P = 0.508). The relative power drop (P = 0.041) differed significantly among the ACTN3 genotypes, and non-significant differences in peak power and average power. The relative left hand grip strength in male (P = 0.004) differed significantly between the ACTN3 R allele. However, non-significant differences right hand grip strength in male and both hand grip strength in female. We found a positive relationship between the ACTN3 R577X genotypes and the relative left hand grip strength in male Korean National combat athletes. Our data indicate that the ACTN3 R allele (RR and RX genotypes) is associated with muscle strength output capacity.